Difusão de inovações, estratégia e a inovação: a construção de um modelo orientativo para os gestores de empresa - Gomes, Francisco Rodrigues (2008)
The current article was developed with the objective of provide a contribution to build an analysis framework model inside of business view. The present article is concern on an essay and its composed trough straightforward revision of description referential, with concept analysis of some aspects related on strategy theory of Treacy and Wiersema (1995) and Hax e Wilde (2001), Innovation theory of Christensen(2003) and the concept of life of diffusion of innovations of Rogers(19621) and the current work is address to identify the appropriate innovation and strategy composition according to the moment of life cycle of market, with proposition of bring to context of innovative and strategy decisions, the dynamic impact that facing day-by-day companies